An investigation into the rising incidence of carcinoma of the prostate in Canada. - Levy, Isra Gabriel. (University of Ottawa (Canada), 1993)
Objectives. The purpose of this study was to analyze prostate cancer trends in Canada, determine whether the observed trends are associated with earlier detection, assess the association between prostatectomy rates and prostate cancer incidence rates and assess other possible reasons to explain the observed trends. Conclusions. Correlations between prostate cancer incidence rates and prostatectomy rates suggest that increased surgical treatment of benign prostatic disease contributed to the increase in incidence rates through increased detection of latent cancers. This hypothesis is supported by the chart review, which is the first work to show an association, other than an ecological one, between TURPs and the increased detection of prostate cancer. The increase in early stage cancers, especially incidentally discovered cancers, and the discovery of increased scrutiny of surgical specimens by histopathological staff, corroborates the ecological data. Although elevations in unestablished risk factors may have contributed to the observed increase in incidence, much of the increase can be attributed to an increase in rates of localised disease. This suggests that the increases may be due to early detection and not risk elevation. (Abstract shortened by UMI.)
Keywords: Health Sciences, Public Health.